2015
DOI: 10.1590/s0036-46652015000300007
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between Herpesvirus Detection in Saliva and Gingivitis in Hiv‑infected Children

Abstract: The aims of this study were to compare the detection of human herpesviruses (HHVs) in the saliva of HIV-infected and healthy control children, and to evaluate associations between viral infection and gingivitis and immunodeficiency. Saliva samples were collected from 48 HIV-infected and 48 healthy control children. Clinical and laboratory data were collected during dental visits and from medical records. A trained dentist determined gingival indices and extension of gingivitis. Saliva samples were tested for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
1
8
0
1
Order By: Relevance
“…126 On the contrary, high HSV-2 salivary detection rates have been reported among Brazilian HIV-infected and healthy children (4.2% and 8.3%, respectively). 127 HSV-2 may not be detected in the saliva of HIV-seropositive persons undergoing highly active antiretroviral therapy. 128 Based on a study on herpesvirus prevalence among 16-year-old Swedish girls, it was suggested that "transmission of herpesviruses is common in adolescence, and sex, even with regard to its close association with kissing, is one important determinant" 129 ; however, in that series antibodies to HSV-2 were seen only in 1% of participants, and to date kissing transmission has not been reliably demonstrated.…”
Section: Herpes Simplex Virus Type 1 (Hsv-1; Hhv-1)mentioning
confidence: 94%
“…126 On the contrary, high HSV-2 salivary detection rates have been reported among Brazilian HIV-infected and healthy children (4.2% and 8.3%, respectively). 127 HSV-2 may not be detected in the saliva of HIV-seropositive persons undergoing highly active antiretroviral therapy. 128 Based on a study on herpesvirus prevalence among 16-year-old Swedish girls, it was suggested that "transmission of herpesviruses is common in adolescence, and sex, even with regard to its close association with kissing, is one important determinant" 129 ; however, in that series antibodies to HSV-2 were seen only in 1% of participants, and to date kissing transmission has not been reliably demonstrated.…”
Section: Herpes Simplex Virus Type 1 (Hsv-1; Hhv-1)mentioning
confidence: 94%
“…In PLWH with gingivitis, Pg and CMV presented higher frequency in subgingival plaque (95.6% and 91.3%, respectively ( p < .0005), and Tannerella (47.8%) and EBV (78.3%) were detected in subgingival plaque and saliva (52.2% and 52.2%, p < .005) (Grande et al., 2011). Interestingly, HIV‐positive children with gingivitis attending a dental school in Rio de Janeiro demonstrated similar low levels of HSV compared to HIV‐negative children with gingivitis (6.2%), twice as much CMV (25% vs. 12.5%), with no EBV or varicella‐zoster virus (Otero et al., 2015).…”
Section: Question 4: What Are the Impacts Of Human Herpesviruses And mentioning
confidence: 99%
“…In our study, we found an overall prevalence of 35.2% of EBV in tissue biopsies from gingivitis and periodontitis, which is compatible to the described prevalence in the literature 10 . A recent study has failed to detect EBV in saliva from HIV-infected children with gingivitis in Brazil 2 . However, it is known that several factors can influence the viral detection in periodontitis, including the sample type, methodological approaches and geographical/ethnical differences regarding the herpesviruses occurrence 10 .…”
mentioning
confidence: 99%
“…Some viral agents have been associated with the pathogenesis of oral lesions in immunocompetent and immunosuppressed individuals, especially DNA viruses such as papillomaviruses and herpesviruses 1 . It has been postulated that the latter group triggers tissue damage which is further increased by the host inflammatory response 2 , creating an enabling an environment for the replication/reactivation of viral agents that may contribute to the pathogenesis of oral lesions 3 . However, the effect of the viral association in tissue damage is uncertain.…”
mentioning
confidence: 99%
See 1 more Smart Citation